Preparation of AlSb thin films by magnetron sputtering technology and its deliquescence mechanism. (January 2019) - Song, Huijin; Gu, Peng; Zhu, Xinghua; Yan, Qiang; Yang, Dingyu
Abstract: In this paper, the AlSb films were successfully prepared by direct-current (DC) magnetron sputtering technology and the deliquescence process and mechanism of AlSb films were investigated, moreover, the function of Cu membrane deposited on AlSb films was simply explored. It suggested that deliquescence processes of films were essentially local deliquescence and further formed some sand holes, ultimately, AlSb films fall off from the quartz glass substrate as increase in contact time between AlSb films and ambient air. Meanwhile, compared to bare AlSb films, Cu deposited on AlSb films could effectively prevent the appearance of sand holes in the specific conditions and the way of annealing treatment further improved the stability of AlSb films.